2021
DOI: 10.3389/fimmu.2021.732549
|View full text |Cite
|
Sign up to set email alerts
|

Human Wharton’s Jelly-Derived Mesenchymal Stromal Cells Primed by Tumor Necrosis Factor-α and Interferon-γ Modulate the Innate and Adaptive Immune Cells of Type 1 Diabetic Patients

Abstract: The unique immunomodulation and immunosuppressive potential of Wharton’s jelly-derived mesenchymal stromal cells (WJ-MSCs) make them a promising therapeutic approach for autoimmune diseases including type 1 diabetes (T1D). The immunomodulatory effect of MSCs is exerted either by cell-cell contact or by secretome secretion. Cell-cell contact is a critical mechanism by which MSCs regulate immune-responses and generate immune regulatory cells such as tolerogenic dendritic cells (tolDCs) and regulatory T cell (Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
(72 reference statements)
1
6
1
Order By: Relevance
“…Contrary to what was observed by Mrahleh et al [59] in an in vitro study of hWJ-MSCs, no increase in IL-10 concentration was observed in the cell therapy groups. However, this cytokine increased slightly in the OH group than in the untreated eyes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to what was observed by Mrahleh et al [59] in an in vitro study of hWJ-MSCs, no increase in IL-10 concentration was observed in the cell therapy groups. However, this cytokine increased slightly in the OH group than in the untreated eyes.…”
Section: Discussioncontrasting
confidence: 99%
“…This increase can be observed in stressful situations such as immune reactions, inflammation, ischemia, hypoxia, and oxidative stress [64]. In contrast, the OH group that received hWJ-MSCs showed a decrease in the level of this cytokine, which is consistent with other reports [59]. These findings demonstrated the potential immunomodulatory effects of these cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, our quantitative study showed that multiple IV injections of the sEVs over days can be needed to reach quantitative maximum healing that is produced by single MSC injections (Nakazaki et al, 2021). More clinical studies of similar benefits of MSC and MSC-EVs in patients have been published (Weiss et al, 2013;Nassar et al, 2016;Stolk et al, 2016;Mrahleh et al, 2021) Currently, there are 199 listed NIH clinical trials involving MSC, 52 trials on sEVs, some with MSC-secreted EVs, that are now just beginning to come to favorable published conclusion.…”
Section: Msc-sevs Have Proven Healing Ability In Many Chronic Immune ...mentioning
confidence: 78%
“…Mesenchymal stem cells (MSCs) play important roles in regenerative medicine due to their potential for self-renewal and multi-directional differentiation [ 1 ]. MSCs were also found to have strong immunoregulation capabilities caused by the secretion of various signal factors or cell to cell contact [ 2 ].…”
Section: Introductionmentioning
confidence: 99%